Inklyuziv tálimniń innovacialıq paradigması: sociallastırıw, integraciyalıq qatnasıqlar hám imkaniyatlardı institucionlastırıw (SCIENCE and SOCIETY, 2025)
The article provides information on technologies for improving the effectiveness of inclusive and home-based education. In particular, interactive platforms and teaching methods were mentioned for engaging students with disabilities in education.